Effect of IFRS adoption and corporate governance practices on performance: A study on listed companies in Dubai - Al-Khuzaie, Abbas Saad Hamada (2016)
This study has been conducted on the financial market of Dubai. The purpose of the study is to understand the effect of IFRS adoption along with corporate governance characteristics over the financial performance of listed companies in Dubai. The study has taken return on assets as the measurement of performance, while IFRS adoption, board independence, board size, and audit quality as the measurement of CG. Firm size and leverage have been taken as control variables. The data has been collected from the annual reports and websites of the companies. Regression analysis is employed to understand the effect of each independent variable on performance. The study has identified that IFRS adoption; board independence, board size, and audit quality have a significant effect over financial performance of companies listed in Dubai stock market. The major contribution of the study is the combined effect of variables, as in the available literature all these variables have not yet been studied collectively.